Metaphysical Times Ostara 2022 - Ireland, Terri; Tschauder, Rick; Schein, Lorraine; Kadapa, Shashi; Ackley, Ginger; Tidwell, Elizabeth; Gardner, Emma; Kohout, Ed; Mueller, Leah; Imaginator; Vale, Nixie (Metaphysical Times, 2022)
The volume begins by discussing the spring (Vernal) equinox and how it was celebrated by the ancient Celts in Ireland and Scotland. Then moves to the symbolism of fire in Hindu mythology. Next music in magic is discussed and how it impacts spells that are cast. The volume then continues by discussing why the goddess Ostara is used for the Vernal equinox. Some books are reviewed for aspiring witches and give advice on books to purchase.
This item contains 1 PDF with 16 pages a title page and a table of contents
Keywords: Apatite; Astrology; Chants--Psychological aspects; Crystals; Fire--Folklore; Gaia's Workshop (Gresham, Or.); Fire--Symbolic aspects; Hindu mythology; Moon River Magical Gifts (Canyon Lake, Tex.); Music -- Occult aspects; Nchantments (Gourock, Scotland); Ostara; Sunpath, DawnStar, 1953-2021; Tarot readings; Vernal equinox; Ēostre (Germanic goddess)